The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-35550-w
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial patterns of mitochondrial haplotype and species distributions in Siberian larches inferred from ancient environmental DNA and modeling

Abstract: Changes in species’ distributions are classically projected based on their climate envelopes. For Siberian forests, which have a tremendous significance for vegetation-climate feedbacks, this implies future shifts of each of the forest-forming larch (Larix) species to the north-east. However, in addition to abiotic factors, reliable projections must assess the role of historical biogeography and biotic interactions. Here, we use sedimentary ancient DNA and individual-based modelling to investigate the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 55 publications
10
54
1
Order By: Relevance
“…In the case of the population history of L. sibirica and L. gmelinii in their contact zone, Semerikov et al (2013) found evidence for the asymmetric introgression of L. sibirica mitotypes in a population carrying only L. gmelinii chlorotypes, confirming the natural invasion of L. gmelinii into the range of L. sibirica. Here we corroborate these findings with a distinct discrepancy between relatively high rates of L. sibirica mitotypes as reported before (Epp et al, 2018) and low rates of L. sibirica in the chloroplast reads found in this study. This points to an invasion of L. gmelinii in a former population of L. sibirica prior to the date of our oldest sample (6700 cal-BP).…”
Section: Sibirica Variants Present Over Timesupporting
confidence: 91%
See 4 more Smart Citations
“…In the case of the population history of L. sibirica and L. gmelinii in their contact zone, Semerikov et al (2013) found evidence for the asymmetric introgression of L. sibirica mitotypes in a population carrying only L. gmelinii chlorotypes, confirming the natural invasion of L. gmelinii into the range of L. sibirica. Here we corroborate these findings with a distinct discrepancy between relatively high rates of L. sibirica mitotypes as reported before (Epp et al, 2018) and low rates of L. sibirica in the chloroplast reads found in this study. This points to an invasion of L. gmelinii in a former population of L. sibirica prior to the date of our oldest sample (6700 cal-BP).…”
Section: Sibirica Variants Present Over Timesupporting
confidence: 91%
“…When comparing the ancient reads to chloroplast reference genomes from L. gmelinii and L. sibirica, the great majority of reads carry the L. gmelinii variants with a low frequency of L. sibirica variants in all four samples. In contrast, the analysis of one mitochondrial marker derived from the same core by Epp et al (2018), showed a mixture of both species, with relatively high rates of L. sibiricaexcept for the most recent sample, which showed clear dominance of the L. gmelinii mitotypepointing to a co-occurrence of both species across most of the sediment core. In the genus Larix, chloroplasts are predominantly inherited paternally (Szmidt, Aldén, & Hällgren, 1987) whereas mitochondrial DNA is inherited maternally (DeVerno, Charest, & Bonen, 1993), a phenomenon which has been reported for almost all members of the conifers (Neale & Wheeler, 2019).…”
Section: Sibirica Variants Present Over Timementioning
confidence: 85%
See 3 more Smart Citations